AXL is a Putative Tumor Suppressor and Dormancy Regulator in Prostate Cancer - Axelrod, Haley D. (Mol Cancer Res, 2018)
Prostate cancer bone metastasis remains lethal and incurable, and often arises years after elimination of the primary tumor. It is unclear what underlies the decades-long clinical latency before recurrence, but evidence points to the existence of dormant residual tumor cells that disseminated before the primary tumor was eliminated. To design therapies to prevent progression of disseminated tumor cells (DTCs) into lethal metastases, it is crucial to understand the mechanism(s) underlying this dormancy. The current study functionally validated our previous observation that implicated the GAS6/AXL axis in mediating DTC dormancy in the bone marrow. AXL-null and AXL-overexpressing prostate cancer cell lines were generated to determine if AXL was necessary and/or sufficient for dormancy. Characterization of these cells in vitro and using in vivo mouse models of DTC growth demonstrated that AXL was indeed sufficient to induce dormancy, but was unable to maintain it long-term and was not absolutely required for a dormancy period. Clinically, AXL expression correlated with longer survival in prostate cancer patients, and AXL was not expressed by cancer cells in primary or metastatic tissue. These data point to a tumor suppressive role for AXL in prostate cancer, and future work is required to determine if AXL is expressed on human bone marrow DTCs.